Polymerase Chain Reaction in African Research Setting: Oppurtunities and Limitations - (:unkn) unknown (My University, 2022)
The polymerase chain reaction (PCR) technique was first discovered in 1985 and has since then shown to be an important tool in the world of research and medical diagnostics. Previous techniques of DNA replication, which relied on microorganisms and may take weeks to complete, have been supplanted by PCR due to its timeliness, as well as its high degree of sensitivity and specificity. Since its invention, the PCR has played many roles in specimen analysis, mutation analysis, forensic science and in the human genome project, among others. While the developed nations of the world have seized the several opportunities that lie in the utilization of the polymerase chain reaction technique to advance the field of medicine and research, many Africa countries just seem to be scratching the surface in its use. The advent of COVID-19 in the last two years has brought about an increase in the awareness of the technique and brought to light the fact that many African countries are ill-equipped with the adequate tools to meet the challenges of the world of medical sciences and research. This review aims to give an insight into the opportunities that exist with the use of PCR and the limitations that may hinder these opportunities especially among developing countries in Africa.
Keywords: African Research